Association of Intrahepatic Cholestasis of Pregnancy with Adverse Fetal Outcome (Medical Forum Monthly, 2020)
Objective: To determine association of intrahepatic cholestasis of pregnancy with adverse fetal outcome.Study Design: Cohort StudyPlace and Duration of Study: This study was conducted at the Department of Gynecology and Obstetrics of PAEC General Hospital Islamabad from August 2015 to Feb 2016.Materials and Methods: 110 patients were included in the study during second trimester according to inclusive criteria. Two groups with 55 patients each were made. Group A was assigned to the patients with deranged LFTs while Group B was assigned to the patients with normal LFTs. Patients were followed during third trimester. Adverse outcomes like preterm labor and meconium stained liquor were the parameters observed in both groups and these were compared between groups.Results: Total 110 patients were included in study. Mean age was 27.89 + 4.51 years. Out of all 110 patients included in study 27 (24.5%) were prim gravida, 33 (30%) had one pregnancy earlier and 50 (45.5%) had 2 or more pregnancies. In group A 14 patients were prim gravida, 14 had one pregnancy earlier and 27 and more than two pregnancies. In group B 13 patients were prim gravida, 19 had one pregnancy earlier and 23 had two or more pregnancies earlier. In group A mean ALT was 132.75 U/L, AST was 132.04 U/L, ALP was 1049.96 U/L and Bilirubin was 2.34mg/ dL. While in Group B, mean ALT was 28.71 U/L, AST was 28.51 U/L, ALP was 622.69 U/L and Bilirubin was 0.931 mg/dL. In Group A, 35 patients (63.63 %) had meconium stained liquor while in Group B, only 07 patients (12.72%) had meconium stained liquor. In Group A, 32 patients (58.18 %) had Preterm Labor while in Group B, only 07 patients (12.72%) had Preterm Labor.Conclusion: ICP is a condition that can affect the fetal outcomes and can cause preterm labor and meconium staining as compared to normal pregnancy. Adverse fetal outcomes are not associated with age and parity.